FÆLLESSPISNING MIDT I JYLLAND: Når det drejer sig mere om spisning og drikning end om mad og drikke - Jenkins, Richard P. (Tidsskriftet Antropologi, 1998)
Richard P. Jenkins: Sociability in Mid- Jutland: When Eating and Drinking is the Point, rather than Food and Drink This paper is based upon nearly a year’s field research in a town in mid-westem Jutland, Denmark. Ethnographic data is presented about the range of occasions for eating and drinking which are available to its inhabitants: eating at home, meetings, annual general meetings, parties and celebrations, and public eating on demand and at need. The argument is made that the social occasions of eating and drinking are more significant than the food and drink itself. This is related to a complex of cultural values concemed with sociability, consensus, mutuality, communality and apparent equality, which finds its widest expression in the Danish welfare State. Developing changes in the structure of private life and households - and in the values just itemised - are related to changes in the organisation of eating and drinking. A more general argument is also offered, about the need to re-orient the study of food and drink towards a processual study of eating and drinking.